Comprehensive analysis of peripheral blood free amino acids in MASLD: the impact of glycine-serine-threonine metabolism - Masaaki Mino; Eiji Kakazu; Akitoshi Sano; Mio Tsuruoka; Hiroko Matsubara; Keisuke Kakisaka; Takayuki Kogure; Katsunori Sekine; Yoshihiko Aoki; Masatoshi Imamura; Michitaka Matsuda; Taiji Yamazoe; et al. (Amino Acids)
Abstract Little is known about how blood free amino acids (FAAs) change in metabolic dysfunction-associated steatotic liver disease (MASLD). This study aims to identify the imbalance of FAAs in MASLD and explore its correction as a potential therapeutic target. We analyzed plasma FAAs data from 23,036 individuals with steatosis information from a biobank in Japan, and 310 patients with MASLD were enrolled. According to diagnostic criteria for steatotic liver disease (SLD) or cardiometabolic criteria (CC), we divided the subjects into five groups: MASLD, metabolic dysfunction and alcohol-associated liver disease (MetALD), CC-SLD-, CC + SLD-, and CC-SLD + . Twenty FAAs were compared among these groups and among MASLD patients with pathological information. Among the 20 FAAs, the levels of 16 FAAs increased in CC + SLD- according to the number of matches with CC items associated with insulin resistance (IR). Steatosis enhanced most of these changes but serine (Ser) and threonine (Thr) were unaffected. Glycine (Gly), Ser and Thr were significantly decreased in patients according to steatosis grade. We investigated the association between these FAAs imbalances and pathogenesis using MASLD mouse models. In mice fed a high-fat, fructose, and cholesterol (FFC) diet, metabolomics and RNA sequencing analyses indicated that abnormality in Gly, Ser, and Thr metabolism in the liver was associated with mitochondrial dysfunction and enhanced glycolysis via pyruvate. High-Gly, Ser, and Thr diet ameliorated pathogenesis of MASLD in leptin-deficient mice. Most FAAs increase due to cardiometabolic abnormalities, particularly IR. However, interventions targeting the metabolism of Gly, Ser, and Thr have the potential to improve MASLD.